MEDIA DAN POLITIK (Mencari Independensi Media Dalam Pemberitaan Politik) - Vellayati Hajad (SOURCE : Jurnal Ilmu Komunikasi, 2016)
This article explains about the relation of media and politics and how the position ofhow the media position in Indonesian politics. Shoemaker and Reese have twoapproaches see the media , namely passive and active . The passive approach occurs when the media represent reality without distortion . Active approach is when the media come to frame social reality into the reality of media. The second approach is what makes media are not neutral and do tend to be biased in their reporting because the media no longer represent the event as a whole but with some viewpoints that are considered attractive. It is often also referred to as media manipulation. The media in a democracy should be able to independently and not closer to the government and the market.Keywords: Media, Politics and Democratization